Ecologia de saberes sobre agrotóxicos e sustentabilidade: o lugar do Direito entre uma abordagem interdisciplinar com seres humanos e decisões judiciais de Cortes Constitucionais na Argentina, Brasil e Paraguai - Pillon, Leonardo Ferreira (2019)
Our research is a study about local perceptions on the matter of agrotoxins and sustainability taken place in 5 agroecology and agribusiness events between the years 2017/2018 in the region of the 30 pueblos misioneros (Argentina, Brasil and Paraguay) where we compare with reflexive cases from the constitutional jurisdiction on the subject by Federal Supreme Tribunal (BRA), Supreme Court of Justice of the Argentinian Nation (ARG) and Supreme Court of Justice (PY). The issue that moves the investigation is: “What are the limits and possibilities of empiric analysis, from the Law, the power relations discursivelly constructed on the subject of agrotoxins and sustainability between Constitucional Courts and local knowledges from some events of agroecology and agribusiness that take place in the 30 pueblos misioneros?” We interview 68 people, from which 19 was realized in Department of Itapúa (PY), 17 in Misiones Province (ARG) and 32 in State of Rio Grande do Sul (BRA). We conclude that the judicial actuation is indifferent to the social results of its function, this power-duty reminds throughout the Law regime of truth the lack of accountability of corporations, technoscience and fraction of the technique knowledge co-protagonist of its own regime of truth. Finally, we point out possibilities to mean the Law on the subject of agrotoxins and sustainability from de South perspectives where the laws theoretical references still the same of modernity.